ELECTRONIC MEDICAL RECORD, A MEDICAL SERVICE CHALLENGE IN 4.0 ERA AND ITS LEGAL ASPECT - Gizela, Beta Ahlam (Jurnal Forensik dan Medikolegal Indonesia, 2020)
Background: All people need health services. As a concequences of that, we found great number of patients queue in public healh services. To reduce the patients queue, technology implemented. Electronic medical record is one of technology aplication that able to solve the problem of queueing. Indonesia has no special regulation on electronic medical record. Considering that background, author try to explore problems in implementation of electronic medical record, 1) is the electronic medical record valid as an evidence in litigation process (ethics and law) and 2) is electronic medical record able to provide information needed in patient management. Objective: Justification proofing of ethicolegal judgement in technology implementation of medical record documentation. Methods: This research uses mixed methods design: Quantitative method leading to in-depth ethically reflective method after coherent qualitative result. Populations of the research are outpatients, and the subject of this research are health workers of hospital that use electronic medical record. Results: Electronic medical record used is “computerized” or “automated” medical record. There are some paperless documents, combining with conventional record in implementation. There is significant difference on accessability and completeness between electronic medical record and conventional medical record. Electronic medical record able to improve the service quality, in beneficence and non-maleficence principle. There is no significant difference on legal quality between electronic medical record and conventional medical record. Implementation of automated medical record is an inter phase, before a hospital successfully implement fully electronic medical record. Conclusion: Automated medical record able to improove quality of medical record, based on beneficence and non-maleficence ethics principle. It’s needed further investigation to conclude autonomy and justice principle nowadays.